SPRING‐RIO TSE: 2D T2‐Weighted Turbo Spin‐Echo brain imaging using SPiral RINGs with retraced in/out trajectories. Issue 2 (8th April 2022) - Wang, Zhixing; Allen, Steven P.; Feng, Xue; Mugler, John P.; Meyer, Craig H.
Abstract : Purpose: To develop a new approach to 2D turbo spin ‐echo (TSE) imaging using annular spiral rings with a retraced in/out trajectory, dubbed "SPRING‐RIO TSE", for fast T2 ‐weighted brain imaging at 3T. Methods: A long spiral trajectory was split into annular segmentations that were then incorporated into a 2D TSE acquisition module to fully exploit the sampling efficiency of spiral rings. A retraced in/out trajectory strategy coupled with spiral‐ring TSE was introduced to increase SNR, mitigate T2 ‐decay induced artifacts, and self‐correct moderate off‐resonance while maintaining the target TE and causing no scan time penalty. Model‐based k‐space estimation and semiautomatic off‐resonance correction algorithms were implemented to minimize effects of k‐space trajectory infidelity and B0 inhomogeneity, respectively. The resulting SPRING‐RIO TSE method was compared to the original spiral‐ring (abbreviated "SPRING") TSE and Cartesian TSE using simulations, and phantom and in vivo acquisitions. Results: Simulation and phantom studies demonstrated the performance of the proposed SPRING‐RIO TSE pulses sequence, as well as that of trajectory correction and off‐resonance correction. Volunteer data showed that the proposed method achieves high‐quality 2D T2 ‐weighted brain imaging with a higher scan efficiency (0:45 min/14 slices versus 1:31 min/14 slices), improved image contrast, and reduced specific absorption rate compared to conventional 2D Cartesian TSE. Conclusion: 2D T2 ‐weighted brain imaging using spiral‐ring TSE was implemented and tested, providing several potential advantages over conventional 2D Cartesian TSE imaging.